ANALISIS DAN PERANCANGAN SISTEM INFORMASI PADA PT. MENARA GADING PUTIH - Feni Suwanto; Ery Dewayani; Desi Arisandi (Jurnal Ilmu Komputer dan Sistem Informasi, 2014)
PT. Menara Gading Putih (MGP) is a company that is engaged in the service field. The company constructed tracks for oil pipeline. The company is organized into several structures. They are tender, purchasing, project, finance, and human resources development. This company still using manual process for their daily transaction. Because of that, PT. MGP has a problem to implement their transaction like recording data, calculating data, saving data, and many more. To overcome those problems, it’s a must to make a new system that will overcome the problem. Analysis and design information system aim to improve perfomance of the company and help the company to making desicion that will useful in the future. The new design of system is using System Development Life Cycle (SDLC) as a method to design a workplan and literature study and observation as a method to collect samples and data. The design of system can write data of customer, project, purchase, payroll etc and record them into database, make a form or report like proposal, invoices, etc, which will be use at business transaction. Key words Analysis and Design Information System, Company, Information System, PT. MGP,